A new biomechanical approach to side-foot soccer shots` characteristics determination - Massoumi-Mofrad, F.; Shahbazi-Moghaddam, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study considers the biomechanical factors that are relevant to succeed in the kicking of a ball into three points; A, B, and C pre-selected in the area of gate. Sixteen amateur of top university players participated in this study. Two cameras at 30 Hz were used in sagital and frontal planes. The recorded data were processed through computer with Ulead Video Studio and AutoCad softwares. The time of flight, time of ball contact with kicking foot, the angle of volley, ball velocity, and the angle of knee flexion were achieved. Then by biomechanical formulae, ball speed, launch angle, range, force exerted to ball, and finally the torques applied to leg joints; ankle, knee, and hip were obtained. The ball speed, launch angle, and the ball range were theoretically estimated and then verified with the mentioned method.